A study to assess the prevalence of diarrhoea and under five children’s mothers’ knowledge in management of diarrhoea at home with selected home remedies from selected areas of Navi Mumbai - Kambli, Swati; Mane, Nisha; Mistry, Mankumari (Innovational: Journal of Nursing and Healthcare, 2024)
arrhea is often the result of a viral, bacterial or other type of infection. Diarrhoea is the major cause of mortality and morbidity among under five children. So it is important to prevent diarrhoea by use of proper home remedies which is cost effective, hence this study was undertaken to investigate knowledge of mothers. Aim: To assess mothers knowledge in relation to use of selected home remedies and its effect for diarrhoea and its association with demo graphic variables. Method: In this study descriptive explorative design was used for quantitative approach. A total of 100 mothers/caregivers of under five children participated in the study. Result: Majority of mothers of under children had lack of knowledge on effect of home remedies in management of diarrhoea . Conclusion: It is necessary to strive hard to spread awareness about the effect of home remedies on diarrhoea.